Literature Review: Penggunaan Obat Off-label pada Pasien Pediatri - Chintia Dwi Tanasa; Nurma Suri; Citra Yuliyanda Pardilawati; Asep Sukohar (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2025)
Off-label drug use is still widely found, especially among vulnerable patients. Pediatrics is one of the vulnerable patient groups who still often get off-label drug therapy. This study was conducted with the aim of looking at the description of the use of off-label drugs given to pediatric patients. This research is a type of research with the literature review method, with data obtained from several articles, the search for articles was carried out through the Google Scholar database. The results of this study from 10 articles used as research data, found the use of off-label drugs in pediatric patients with the most results in the off-label dosage category and followed by off-label dosage category, off-label age category, and off-label route of administration category, while the off-label contraindication category was not found. Based on the results obtained, it is concluded that the use of off-label drugs in pediatric patients is quite high, so it is necessary to monitor the use of off-label drugs to reduce the incidence of unwanted side effects